Exploring the relationships among online social capital, Internet self-efficacy, mental health, and cyberbully-victim roles in adolescents: a structural equation model - Chen, Qiqi; Guo, Shaolingyun; Chan, Ko Ling (Frontiers in Psychiatry, 2025)
The prevalence and effects of cyberbullying are well-established, while there is sparse evidence addressing the experiences of those in vocational schools. Social capital and self-efficacy have attracted significant public and scholarly interest, but research on these factors in cyberspace remains limited in scope. This study aims to comprehensively investigate the pathways through which online social capital and Internet self-efficacy mediate the development of mental health consequences among adolescent cyberbullying victims. A total of 1,716 students in Grades 8-12 from public and vocational schools in China participated in the study. Structural equation modeling (SEM) was applied to specify the relationships between online social capital, Internet self-efficacy, cyberbullying, and mental health problems. Results showed that 12.12% of students reported themselves as cyber bully-victims. Internet self-efficacy could potentially mediate the effects of cyberbullying victimization and mental health problems in both school settings. Online social capital and Internet self-efficacy play mediating roles in the relationship between cyberbullying and mental health problems in public school samples. No significant effect of online social capital was found in the vocational school sample. The findings provide insights for proactive intervention in developing adequate online social capital and Internet self-efficacy training for cyberbullying prevention. Discussions on differentiated interventions for vocational school students are also presented to inspire future research and practice.